Legal Challenges Regarding Social Media Campaign Regulation in the 2024 Election - Ngazis, Muhammad (KnE Social Sciences, 2025)
This study examines the legal challenges associated with regulating social media campaigns in the context of the 2024 Indonesian general election. With the increasingly massive use of social media in politics, there are legal issues that arise related to political campaigns on these platforms. This study considers challenges such as the spread of false information (hoaxes), attempts to bring down political opponents through detrimental content, and unclear regulations related to social media campaigns. The research method used is a normative analysis focused on existing legislation and a descriptive approach to understand the development and impact of social media campaign practices. The results of this study are expected to provide insight into the legal issues that arise in political campaigns on social media, as well as provide a basis for the preparation of more effective regulations in addressing these challenges in the 2024 election. Laws that can be used to face these legal challenges include Law Number 7 of 2017 concerning Elections and Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE). The provisions in these laws serve as the legal basis for regulating the implementation of campaigns on social media and responding to legal challenges that may arise in the context of the 2024 Election.